The bishop Juan de Palafox and China: the Ming-Qing dynastic change from Mexico - Busquets, Anna (Huarte de San Juan. Geografía e Historia, 2022)
The conquest of China by the Manchus was the first Chinese event with global repercussions, fundamentally because of the information provided by the Jesuits – both from those who were trapped in the country’s civil strife that accompanied the fall of the Ming and those who dedicated a coherent narration as is the case of Martino Martini. However, there is another text dedicated to this subject that must also be taken into account, the History of the conquest of China by the Tartar, written by the Bishop of Puebla de los Ángeles, Juan de Palafox y Mendoza, published posthumously in 1670. Although Palafox never travelled to China, he had access to various sources on the subject, both handwritten and printed. The bishop, seasoned in the analysis of multiple conflicts in Mexico and the Iberian Peninsula, decided to write a work focused on the analysis of the Manchu conquest of China and dedicate a part of it to an ethnological analysis of Manchu society. This article will focus on the analysis of the History and the reasons that led the bishop of Palafox to be interested in China from his bishopric in Puebla de los Ángeles, paying attention both to the sources from which it was used for the story as well as for the historical analysis of this event. In addition, this work will contribute to drawing the perception of Manchu society in the 17th century, based on the description of the main aspects that Palafox collects in his work.
Keywords: Palafox y Mendoza; China; Manchus; Conquest